High‐Performance and Stable Plasmonic‐Functionalized Formamidinium‐Based Quasi‐2D Perovskite Photodetector for Potential Application in Optical Communication. (26th September 2022) - Wang, Tao; Zheng, Daming; Zhang, Jike; Qiao, Jie; Min, Changjun; Yuan, Xiaocong; Somekh, Michael; Feng, Fu
Abstract: Photodetectors play an important role in optical communication systems and are essential to achieve high‐fidelity signal transmission. The emerging formamidinium‐based quasi‐2D layered perovskites have attracted attention in the field due to their excellent photoelectric performance and moisture stability. By optimizing film quality and device engineering a high‐performance flexible photodetector based on formamidinium‐based perovskites ((BA)2 FAPb2 I7 ) is developed, which shows fast response and excellent air‐stability. By introducing the formamidinium chloride as an additive the quality and the crystallinity of the film are improved. In addition, localized surface plasmonic resonances (LSPRs) are introduced by embedding Au nanostructures on the substrate, the LSPRs, in turn, enhance light and matter interaction, which further increases the performance of the device. The optimized devices show an ultimate response speed ≈9 µs as well as outstanding long‐term environmental stability (environmental conditions > 1000 h). Achieving such high dynamic range and stability is to the best of authors knowledge rarely reported. The device shows the highest responsivity of 2.3 A W −1, detectivity of 3.2 × 10 12 Jones, and outstanding flexibility stability. Finally, the prepared photodetector is successfully integrated into an optical communication system and tested. The results suggest that formamidinium‐based quasi‐2D perovskite photodetectors have great potential in optical communication applications. Abstract : Using the formamidinium chloride as an additive the crystallinity and film quality of quasi‐2D (BA)2 FAPb2 I7 perovskite are improved. A flexible photodetector with fast response speed and good environmental stability is fabricated on the plasmonic‐functionalized multilayer. The photodetector is successfully integrated into the optical communication system as a receiver and tested.